Diversity and Concerns of Indian Medicinal Plants: A Scenario - M.V. Patil2*, D. A. Patil1 and (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The paper highlights current status of knowledge on Indian medicinal plant species used in organized systems of medicine, ethnomedicine and modern medicine. It reviews all-pervasive concern of medicinal plants including role of institutions, organizations, government bodies, rules enforced by them, difficulties in field studies, etc. Current needs to reach sustainable development and their conservation are put together pertinently revealing the state of art of Indian medicinal plants. This review will help guide others interested in medicinal plant research, apart from ecologist, traders and industrialists.